Sociedades anônimas: reuniões e assembleias gerais eletrônicas no Brasil - Botteselli, Ettore Alves Rigo de Lima (2016)
The current global dynamics demands fast and precise decisions. The technological development has allowed the creation and enforcement of digital documents. The electronic documents have their validity and enforcement recognized in several countries, including Brazil. One of the elements that enforced the consolidation of the electronic document in our law was the creation of the digital signature trough the digital certificates. That has granted to the digital documents legal certainty in regard to its authorship and origin. The usage of technological methods in corporate acts ensure a higher participation of the administration boards members and shareholders, besides the highest agility in decision making. The adoption of electronic mechanisms to hold such corporate acts, probably, would overcome the issues related to the absence, however the holding of corporate acts only in electronic format may, in some cases, create some uncertainty. The Brazilian corporate law sets forth several procedures and formalities which should be observed and, consequently, may compromise the validity and enforcement of corporate acts only in electronic format, especially the shareholders meeting. Notwithstanding such procedures and formalities, there is still a structure issue in regard to the registries of commerce, which may difficult the settlement of corporate acts only in electronic format